Role of Game-Based Learning in Improving Financial Literacy and Investment Skills Among the Young Generation - Kosasih, Wahid Hasyim; Agus Juhana (Jurnal Pendidikan Ekonomi Undiksha, 2025)
Nowadays, investment skills and financial literacy are very important, especially for the younger generation who realize the value of good financial planning. Investment in stocks and cryptocurrencies can also be a barrier to making wise financial decisions due to their complexity. Game-based Learning can be one of the effective ways to provide interaction and improve investment skills in a safe manner. Relevant studies on the use of financial education games have been reviewed using the Systematic Literature Review method guided by PRISMA. The studies show that simulation-based games can improve analytical, reflective, and decision-making skills. This is implemented with elements of real decision-making simulations, packaged in an interesting story, and played in flexible time. This kind of simulation fosters intrinsic motivation in students while helping to reduce behavioral biases such as overconfidence and disposition effect, and hone financial skills holistically. These types of educational games put students in conditions that are close to reality. Therefore, educational games are very practical in teaching financial education and can significantly improve students' skills, allowing them to face investment challenges with confidence and high competence in a realistic environment.